Do Tariff Rates Have an Effect on Inflation The Causal relationship between the two Evidence from Iceland - Ólafur Freyr Ólafsson 1996- (2018)
In the wake of tariff talks from the United States the goal with this thesis to test what effect the tariff rate have on the economy, and whether it effects the everyday life of the public. To try and find some economic reasons for these tariffs the United States has announced they will levy towards other countries, Iceland was used in this research since the author is Icelandic and because of the lack of research in this are in Iceland. This research asks the question whether there is a causality between tariff rates and inflation in Iceland. Using inflation as a proxy, for consumer prices. Inflation rates and tariff rates from the period 1993 to 2016 where gathered and used as the data in this research. The causality was tested with a Granger-causality test. The Granger-causality can find, if any are to be found, links and direction of those links between the two variables. The results showed no signs of a Granger-causality between the two variables, tariff rates and inflation